ON THE TITRATION OF BACTERIOPHAGE AND THE PARTICULATE HYPOTHESIS - Clark, Harry (The Rockefeller University Press, 1927)
1. The theory of the serial dilution method of titration of bacterio-phage has been worked out on the basis of the simple particulate hypothesis. 2. It has been shown that, if the dilution constant is .1, only about 60 per cent of parallel runs on the same solution should give the same end-point, the average being taken over a great number of titrations of each of a great variety of solutions. 3. The discrepancy between this figure, 60 per cent, and Dr. Bronfenbrenner's estimate, 85 per cent, is considerable. 4. Inasmuch as the particulate hypothesis is well founded, no explanation of the discrepancy is suggested.